(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Structural and comparative analysis of aquatic flora of Eastern Galicya is presented. Systematic, geographical, biological, ecological and coenotic structure are analyzed. It was found that The aquatic flora of the region is found to include 134 species. The localities of rare species are marked. Urgent tasks are outlined for the future.